From embryonic development to human diseases: The functional role of caveolae/caveolin. Issue 1 (17th March 2016) - Sohn, Jihee; Brick, Rachel M.; Tuan, Rocky S.
Abstract: Caveolae, an almost ubiquitous, structural component of the plasma membrane, play a critical role in many functions essential for proper cell function, including membrane trafficking, signal transduction, extracellular matrix remodeling, and tissue regeneration. Three main types of caveolin proteins have been identified from caveolae since the discovery of caveolin‐1 in the early 1990s. All three (Cav‐1, Cav‐2, and Cav‐3) play crucial roles in mammalian physiology, and can effect pathogenesis in a wide range of human diseases. While many biological activities of caveolins have been uncovered since its discovery, their role and regulation in embryonic develop remain largely poorly understood, although there is increasing evidence that caveolins may be linked to lung and brain birth defects. Further investigations are clearly needed to decipher how caveolae/caveolins mediate cellular functions and activities of normal embryogenesis and how their perturbations contribute to developmental disorders. Birth Defects Research (Part C) 108:45–64, 2016. © 2016 Wiley Periodicals, Inc.